Evaluation of Agronomic Performance of Maize Varieties Under Spring Season in Kailali, Nepal - Bhatta, Kailash; Adhikari, Bishnu Bilas; Joshi, Hemant; Bhatta, Ankita (Journal of Agriculture and Forestry University, 2026)
Maize (Zea mays L.) is a key cereal crop for food, feed, and industry, but its productivity in Nepal remains low compared to the global average. In the western Terai, yield of maize is constrained by the limited use of adapted hybrids and the lack of local evaluation. A field experiment was carried out from February to August 2024, in Kailali, Nepal, to evaluate the agronomic performance of spring maize varieties and identify suitable high-yielding options. The experiment was laid in Randomized Complete Block Design (RCBD) with three replications and seven treatments: RH-6, RH-10, RH-12, RH-16, CAH-1511, Arun-2 (OPV check), and Rajkumar (hybrid check). The plot size was 3 m × 3 m with 60 cm × 25 cm plant spacing, and a fertilizer dose of 150:60:60 :: N:P₂O₅:K₂O kg ha⁻¹ along with 4 t ha⁻¹ poultry manure was applied with standard agronomic practices. Data on phenology, growth, yield attributes, and yield were recorded from ten randomly selected plants per plot. Analysis was performed using ANOVA for RCBD and mean separation using Fisher’s LSD at 5% level, along with Pearson correlation analysis. Significant varietal differences were observed for plant height, time to tasseling and silking, length and weight of cob, kernel rows per cob, kernels per row, thousand kernel weight, grain yield, stover yield, biological yield, and harvest index. RH-10 recorded the highest test weight (353.26 g), while Rajkumar had the heaviest cobs (301.77 g). Grain yield was found to be highly and positively correlated with the number of kernel rows per cob, cob weight without husk, length of cob without husk, test weight, biological yield, and harvest index. CAH-1511 produced the highest grain yield (7.69 t ha-¹) and benefit-cost ratio (2.10), which was followed by RH-10. Overall, CAH-1511 and RH-10 exhibited superior agronomic performance, better yield components, and higher economic returns. Therefore, these varieties are recommended for spring maize cultivation in Kailali under similar agro-ecological conditions.